The Obligations of Notaries in Providing Free Legal Services to Indigent People Based on Law No. 2 of 2014 - Mukti, Sukma Raka Pratama Karyana (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research aims to determine and analyze legal regulations regarding the Notary's obligation to providefree legal services to people who cannot afford it, and uto find out and analyze the legal consequences for Notaries who do not provide free legal services to people who cannot afford it. To achieve the above objectives, the author uses a type of Normative Juridical legal research. The approach method in this legal research uses a statutory approach (Statute Approach) and a conceptual approach (Conceptual Approach). The type of data used in this research is secondary data including words and actions, as well as written data sources. Research data sources consist of primary legal materials, secondary legal materials and tertiary legal materials.The data collection method is used to collect data by means of literature study. The data analysis method uses Descriptive Research. Based on the research results, conclusions were obtained, firstly that Legal regulations regarding the obligation of Notaries to provide free legal services to people who cannot afford them are contained in Article 37 paragraph (1) UUJN and Article 3 paragraph (7) Notary Code of Ethics. Article 37 UUJN and Art3 paragraph (7) Notary Code of Ethics is something that must be implemented, however, because there are no standard rules from INI as the organization that oversees Notaries throughout Indonesia regarding procedures and who can be said to receive legal assistance to determine whether someone is eligible or can be exempt from fees. Second conclusion, the legal consequences for Notaries who do not provide free legal services to people who cannot afford them are sanctions. In terms of administrative sanctions, Notaries can be subject to sanctions in the form of: Government coercion (besturssdwang), Withdrawal of decisions, Imposition of administrative fines, Imposition of forced money by the government (dwangsom). Meanwhile, the sanctions contained in Article 37 paragraph (2) UUJN are in the form of: verbal warning, written warning, temporary dismissal, honorable dismissal and/or dishonorable dismissal. Sanctions contained in Article 6 paragraph (1) of the Notary Code of Ethics include: reprimand, warning, temporary dismissal from Association membership, honorable dismissal from Association membership, and/or dishonorable dismissal from Association membership. Keywords: Incapacitated; Obligations; Services.